A survey of the current nurse practitioner and physician assistant workforce in Dutch ambulance care - Risco van Vliet; Geert-Jan Deddens; Rogier Evenhuis; Xavier R.J. Moors (Elsevier, 2022)
Background: Dutch ambulance service faces future challenges due to acute care development, patient changes, demographics, increased ambulance runs and regional differences. Ambulance Care Netherlands published a framework titled "Pilot physician assistant and nurse practitioner ambulance care". Within this framework, a role is proposed so that their qualifications can provide solutions to future challenges. Despite the introduction of nurse practitioners and physician assistants into Dutch ambulance care, little is known about the effects of this introduction or the tasks these professionals perform. Nevertheless, they are being called upon, even though it is not known whether their potential contribution to the desired outcome described in the framework Objective: This study aims to provide an overview of all nurse practitioners and physician assistants working in Dutch ambulance care and the tasks they perform. Design: We used a cross-sectional exploratory study design. The nurse practitioners and physician assistants participated in a structured telephone survey. Setting: Emergency ambulance services in the Netherlands Participants: A total of 56 respondents participated in a telephone survey. Results: We found 53 nurse practitioners and 20 physician assistants working in Dutch ambulance care, 56 participated in the survey. Their performance of both direct care and indirect care tasks differed considerably. While some nurse practitioners and physician assistants were fully autonomous in-patient care, others were bound by regulations and restrictions. Conclusions: We found large variations between respondents in direct and indirect care task, number of working hours, and the different positions within the different Emergency ambulance services in the Netherlands. As a result, the established framework cannot presently function but can provide sound guidance to different ambulance services in positioning their nurse practitioners or physician assistants.